To translate the line given by the equation \( y = 3x + 2 \) one unit to the right and two units up, we will perform the following steps:
-
Shift One Unit to the Right:
- To shift a graph one unit to the right, we replace \( x \) with \( x - 1 \).
- The new equation becomes: \[ y = 3(x - 1) + 2 \]
- This simplifies to: \[ y = 3x - 3 + 2 \] \[ y = 3x - 1 \]
-
Shift Two Units Up:
- To shift the graph two units up, we add 2 to the entire equation.
- Therefore, we take the modified equation \( y = 3x - 1 \) and add 2: \[ y = 3x - 1 + 2 \]
- This results in: \[ y = 3x + 1 \]
Thus, the equation of the translated line is: \[ y = 3x + 1 \]